Evaluation of a tailored oral health promotion intervention for Syrian former refugees in New Zealand. (14th September 2022) - Al Naasan, Zeina; Broadbent, Jonathan; Smith, Moira; Duncan, Warwick
Summary: To investigate a health promotion strategy to improve oral health among former refugees in New Zealand. Former refugees were recruited ( n = 63) and answered a questionnaire about their oral home care, smoking, sugar consumption and use of dental services. Participants then joined either focus group sessions to co-design oral health educational material ( n = 39) or to be dentally examined for oral hygiene, periodontal health, gingivitis and dental caries and receive motivational instructions to improve their oral health habits ( n = 20). Health messages using dual-language leaflets (covering oral home care, smoking, diet and access to services) were subsequently individually delivered monthly to all participants via a mobile phone application. After 6 months, follow-up questionnaires were sent to all participants and those who had been dentally examined were re-examined. Half of those who did not brush twice daily at baseline (54.1%) had increased brushing to at least twice daily by follow-up; 76.9% of those who consumed sugary drinks at least twice daily, reduced their sugar intake. No smokers quit smoking, however, 52.4% reported reducing the number of cigarettes or engaging in smoking cessation activities. Among those who had been dentally examined, plaque scores, gingivitis and periodontal pocketing all decreased significantly. Culturally and linguistically tailored oral health promotion interventions led to improved oral health behaviours for this group of former refugees over a 6 months follow-up period. We expect this to not only improve the oral health quality of life for this population, but also reduce the burden on the health system. Lay Summary: Refugees have high rates of oral health problems and face hardships in accessing available dental services. This project intended to promote better oral health knowledge and self-care in a group of Syrian refugees that are resettled in Dunedin, New Zealand. We recruited 63 Syrian former refugees who answered a questionnaire on their oral home care, smoking, sugar consumption and use of dental services. A group of 39 people took part in focus group meetings to help design oral health educational material in both the Arabic and English languages. The remaining 20 were dentally examined for periodontal health, dental caries, gingivitis and oral hygiene. All participants received individual monthly oral health messages taken from the leaflets designed with the focus group participants. After 6 months, the same people answered follow-up questionnaires and those who had been dentally examined were re-examined. Participants reported significantly more favourable oral health attitudes and behaviours at follow-up, and oral health among those who had been clinically examined was greatly improved. Oral health education resources tailored to the language and culture of former refugees may help to improve oral self-care and health.